2014
DOI: 10.1016/j.ultsonch.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and sonochemical synthesis of porous (Ce,Zr)O2 mixed oxides from metal β-diketonate precursors and their catalytic activity in wet air oxidation process of formic acid

Abstract: Porous (Ce0.5Zr0.5)O2 solid solutions were prepared by thermolysis (T=285 °C) or sonolysis (20 kHz, I=32 W cm(-2), Pac=0.46 W mL(-1), T=200 °C) of Ce(III) and Zr(IV) acetylacetonates in oleylamine or hexadecylamine under argon followed by heat treatment of the precipitates obtained in air at 450 °C. Transmission Electron Microscopy images of the samples show nanoparticles of ca. 4-6 nm for the two synthetic approaches. The powder X-ray diffraction, scanning electron microscopy, energy dispersive X-ray and μ-Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The characteristic diffraction peaks of CeO 2 in CuO/CeO 2 were slightly broadened compared with that in CeO 2 . This might be associated with the incorporation of Cu 2+ ions with a smaller ionic radius (0.73 Å) compared with Ce 4+ (0.97 Å) (Cau et al, 2014). These phenomena indicated that lattice constriction occurred in CuO/CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic diffraction peaks of CeO 2 in CuO/CeO 2 were slightly broadened compared with that in CeO 2 . This might be associated with the incorporation of Cu 2+ ions with a smaller ionic radius (0.73 Å) compared with Ce 4+ (0.97 Å) (Cau et al, 2014). These phenomena indicated that lattice constriction occurred in CuO/CeO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 5, a strong peak at 462 cm −1 was observed, which was attributed to the vibration mode of the F2 g symmetry in cubic fluorite CeO 2 lattice. This peak of CuO/CeO 2 presented a red shift compared to pure CeO 2 because of the reduction in the lattice parameter as a result of shorter M-O bond length (Cau et al, 2014). The weak band at 1,172 cm −1 was assigned to the second-order phonon mode of fluorite structure.…”
Section: Resultsmentioning
confidence: 99%
“…Sonochemistry has been proven to be green and cost-effective method [22] for the synthesis and coating of nano-sized metal-oxide, composites, and alloys [22][23][24][25][26][27][28]. This technique involves usage of acoustic cavitation phenomenon for the synthesis of different nano/micro-sized materials due to the continuous formation, growth and drastic collapse of bubbles in a solution.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can be employed in many different areas of manufacturing, biotechnology, organic synthesis, and materials chemistry [4,5]. Applications, such as decomposition reactions of precursor compounds lead to the formation of nanoparticles of many important materials, such as metals [6][7][8][9][10], nonmetals [11,12], oxides [13][14][15], chalcogenides [16,17], and phosphates [18][19][20].…”
Section: Introductionmentioning
confidence: 99%